Simultaneous nitrate and organic matter removal from salmon industry wastewater: The effect of C/N ratio, nitrate concentration and organic load rate on batch and continuous process - Huiliñir, C.; Hernández, S.; Aspé, E.; Roeckel, M. (Journal of Environmental Management, 2012)
Abstract: Although simultaneous denitrification-anaerobic digestion has been studied extensively, the use of salmon effluents as organic matter source has received little attention. This study evaluated the effect of C/N ratio, nitrate concentration, and organic load rate (OLR) on simultaneous nitrate and organic matter removal using salmon effluents. The study was carried out in a batch reactor with suspended biomass at 37 °C and pH 7.5, and in continuous biofilm tubular reactors at 37 °C fed with a mixture of a synthetic substrate and a saline protein-rich salmon-plant effluent. The results of the batch and continuous experiments showed that nitrate abatement was greater than 95% at all the studied C/N ratios, without effect of the C/N ratio on NO–N transformation and ammonia production. An increase of nitrate concentration increased organic matter consumption as well as the hydrolytic rate. The organic matter reduction varied between 88% and 40% in the continuous process. For a continuous process, the increase of the OLR decreases the removal of organic matter.